Grandparenting, filial piety, and well-being of Chinese-American older adults. (October 2022) - Kim, Jeung Hyun
This study explores the association between grandparent caregiving by Chinese-American older adults and their perception of filial care and respect (i.e. filial piety) received from their adult children. Drawing on arguments regarding norms of altruism and reciprocity based on social exchange theory in the context of intergenerational relationships, this study examines whether more active engagement in grandparenting results in higher levels of filial piety among adult children and whether that in turn results in better well-being through reducing loneliness. It uses data from Population Study of Chinese Elderly in Chicago, a survey of the well-being of Chinese-American older adults in Chicago. The results show that more hours of grandparent caregiving relate to higher amounts of filial piety in the view of older parents. However, more pressure to take care of a grandchild from adult children reduces perceived filial piety. Furthermore, grandparent caregiving can reduce loneliness among older adults, and receipt of filial piety mediates the association. Discussion focuses on how grandparent caregiving can strengthen intergenerational relationships while contributing to psychological well-being among older Chinese-American adults. This research contributes to the discussion of normative aspects of the intergenerational solidarity theory and holds policy implications for the promotion of well-being among Chinese-American older adults based on their grandparenting practices.